PENGARUH REVITALISASI FASILITAS WISATA DAN AKSESIBILITAS TERHADAP KEPUTUSAN BERKUNJUNG DI TAMAN MINI INDONESIA INDAH - Wanda Junia Ningrum; Wasino (Human Capital Development, 2025)
The purpose of this study is to determine the effect of revitalization of tourist facilities and accessibility at Taman Mini Indonesia Indah. This study uses a quantitative method. The sampling technique uses the Accidential Sampling Technique for tourists. The data collection technique used in this study is a questionnaire and observation. Data were obtained from 100 respondents/sample selected through non-probability sampling/incidental sampling techniques, namely research techniques based on accidentally meeting researchers during data collection. The results of the study indicate that the Revitalization Variable has a positive and significant effect on the decision to visit Taman Mini Indonesia Indah. This can be seen from the significance of the F Calculate value > F Table or 58.453 > 11.283 and the significance level is 0.001 < 0.05 so is rejected and is accepted, it can be concluded that the Revitalization, Tourist Facilities, and Accessibility variables simultaneously have a significant effect on the decision to visit Taman Mini Indonesia Indah.